KETERWAKILAN PEREMPUAN DI DPRD KABUPATEN BENGKALIS PERIODE 2024-2029 - Delvi, Jeni; Asrida, Wan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
ABSTRACT Democracy guarantees equal rights for every citizen to be involved in politics. Women's representation is an important component in a country, especially in the legislative institution. In accordance with Law Number 7 of 2023 concerning General Elections, women's representation in legislative elections should have the same rights as men's representation and does not need to use the